REGIONAL FOCUS Micro, Small and Medium Enterprises in APEC - Tulus T.H. Tambunan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
Concepts and DefinitionsMicro, small and medium enterprises (MSMEs) are defined based on a number of different criteria, which can include the number of employees, the number of sales or income, and/or the number of assets or capital owned by the business. The classification standards for each criterion can differ according to the sector or industry in which the business operates. Therefore, negara-negara use a combination of criteria, and various standards to meet these criteria, to determine whether a company is classified as MSME. Various institutions in an economy might also be useful for defining MSMEs differently to implement various initiatives directed at MSMEs. Therefore, the definition of MSMEs can vary even in an economy. Given that the definition of MSME reflects the underlying economic characteristics, it is not surprising that the definition of MSME varies substantially throughout the world.